An improved Cauchy number approach for predicting the drag and reconfiguration of flexible vegetation. (September 2015) - Whittaker, Peter; Wilson, Catherine A.M.E.; Aberle, Jochen
Highlights: Cauchy number can determine magnitude of flexible vegetation's reconfiguration. Vogel exponent provides useful measure of the rate at which reconfiguration occurs. A drag force model incorporating these parameters is developed and presented. The model is shown to be valid for full-scale riparian trees. The model is validated against an independent, branch-scale data set. Abstract: An improved model to describe the drag and reconfiguration of flexible riparian vegetation is proposed. The key improvement over previous models is the use of a refined 'vegetative' Cauchy number to explicitly determine the magnitude and rate of the vegetation's reconfiguration. After being derived from dimensional consideration, the model is applied to two experimental data sets. The first contains high-resolution drag force and physical property measurements for twenty-one foliated and defoliated full-scale trees, including specimens of Alnus glutinosa, Populus nigra and Salix alba . The second data set is independent and of a different scale, consisting of drag force and physical property measurements for natural and artificial branches of willow and poplar, under partially and fully submerged flow conditions. Good agreement between the measured and predicted drag forces is observed for both data sets, especially when compared to a more typical 'rigid' approximation, where the effects of reconfiguration are neglected.